The Effect of Back Massage to Blood Pressure in Men with Hypertension - Mandias, Reagen; Stendi, Noni (11th International Scholars Conference, 2018)
Back massage is one of the nonpharmacological therapies and is also included in complementary interventional therapies that can be provided by nurses to enhance relaxation and improve circulation of the blood. That is why back massage can be administered to hypertensive patients. The purpose of this study to determine the effect of back massage to blood pressure in men with hypertension. This study used pre-experimental design with one group pre-test and post-test design. Thirty participants were chosen through purposive sampling. Treatment back massage is given on the back of the participants for 15 minutes for 3 consecutive days. The results showed that back massage can lower blood pressure of the participants both systolic and diastolic. Thus, researchers recommend that back massage therapy can be used to lower blood pressure in man with hypertension.